Psychosocial working conditions and major depression or depressive disorders: Review of studies - Dorota Żołnierczyk-Zreda; Paweł Holas (Nofer Institute of Occupational Medicine, 2018)
In the paper the review of studies on the relationship between clinically and subjectively diagnosed depression and psychosocial working conditions has been conducted. Most of these studies include mobbing and stress at work. A large part of them also points to organizational injustice and restructuring, and single studies - long working hours, and work-life imbalance as potential causes of both depression and depressive disorders among working people. The results of these studies confirm that in particular mobbing and stress at work are associated with an increased risk of mental health problems. The greater the exposure to these factors is, the higher the risk of depression is. It has also been shown in many studies that these associations are stronger amongst women. The results of these studies clearly show the need to make every possible effort to change such working environments, and preferably - to prevent their deterioration in the short term. Med Pr 2018;69(5):573-581